PERNIKAHAN CHILDFREE: TREN REVOLUSI GAYA HIDUP GENERASI MILLENNIAL DI KALANGAN GENERASI Z DAN DAMPAKNYA PERSPEKTIF HUKUM KELUARGA ISLAM - Saini Saini (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Childfree marriages are becoming increasingly common among Generation Z and Millennials, indicating changes in social values and lifestyles. The aim of this research is to identify the main components that influence a couple's decision to marry without children and to evaluate the impact from the perspective of Islamic family law. This qualitative study collects data through participant observation and in-depth interviews. Research shows that economics, health, personal freedom, and concern for the environment are the main factors in marriage decisions not to marry. According to Islamic family law, having children is considered an important goal of marriage. However, there is respect for individual freedom to make decisions that do not conflict with sharia principles. Couples who choose not to have children often face social and religious pressure, but their decision can be considered valid if it is based on compelling reasons such as health or other relevant conditions. The social impact of this decision varies, from support to rejection, but shows a shift in values in modern society, which increasingly values individual life choices. This research provides insight into the dynamics of childless marriage and its implications in the Islamic legal and social context.